Handbook of governmental accounting and finance - Crumbley, D. Larry (New York : Wiley, 1992)
The book enables readers to grasp the intricate accounting that is involved as government expenditures multiply and governments engage in progressively complex transactions.
Cover title on the 1994 supplement: Handbook of governmental accounting & finance.
Includes the following supplements: 1994, 1995.
Includes bibliographical references and index.
aia 09/05/13
Loan
Keywords: Finance, Public -- United States -- Accounting -- Handbooks, manuals, etc